2016
DOI: 10.1051/ocl/2016002
|View full text |Cite
|
Sign up to set email alerts
|

Research on resistance to sunflower broomrape: an integrated vision

Abstract: -Sunflower broomrape (Orobanche cumana Wallr.) parasitization on sunflower was first observed at the end of the 19th century and has continued since then jeopardizing sunflower cultivation in many areas of Europe and Asia. A distinctive characteristic of the O. cumana-sunflower parasitic system is that it is mainly governed by a genefor-gene interaction. This determines complete resistance in the host controlled by dominant alleles at a single locus, which facilitates the management of the resistance for hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Co-existing non-weedy populations might represent an additional source of genetic variation for weedy populations by hybridization (Thorogood et al 2009;Velasco et al 2016)…”
Section: Adaptation From Non-weedy To Weedymentioning
confidence: 99%
See 1 more Smart Citation
“…Co-existing non-weedy populations might represent an additional source of genetic variation for weedy populations by hybridization (Thorogood et al 2009;Velasco et al 2016)…”
Section: Adaptation From Non-weedy To Weedymentioning
confidence: 99%
“…This is best demonstrated in the case of sunflower. O. cumana is so far the only broomrape species in which monogenic resistance was identified in sunflower soon after the onset of the O. cumana problem and was widely exploited in sunflower breeding (Velasco et al 2016). As a drawback, this wide exploitation over large areas of these highly resistant hybrids imposed high selection pressure on the O. cumana populations, leading to the development of races (see Molinero-Ruiz et al 2015).…”
Section: Increased Virulencementioning
confidence: 99%
“…Their development was possible due to the existence of good sources of resistance, especially in wild Helianthus species, with monogenic inheritance in most cases ( Fernández-Martínez et al., 2015 ; Cvejić et al., 2020 ). Genetic resistance to broomrape was introduced into sunflower in the early breeding programs in the former USSR in the first years of the 20th century ( Velasco et al., 2016 ). However, the introduction of new resistance sources was followed by the appearance of new physiological races of the parasite that overcame resistance ( Fernández-Martínez et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in broomrape populations in many countries over the past 15 years have resulted in the formation of new races (G and H) (Skoric et al, 2021). There are totally eight races of O. cumana and various countries commonly reported F, G, and H races (Kaya, 2014) Although it has been reported that molecular marker studies on genetic diversity, population structure, racial identification, gene flow, and virulence genetic mechanisms for broomrape populations are not sufficient (Velasco et al, 2016); Recently, studies of molecular markers with highly informative markers have been increasing. Molecular markers are predominantly selected for genetic characterization studies due to having advantages like their abundance in number, unaffected characteristics by environmental factors, or the developmental stage of plants.…”
Section: Introductionmentioning
confidence: 99%